Effects of Li+ substitution on the structural and magnetic properties of Co0.5Mn0.5Fe2O4 particles. Issue 1 (January 2016) - Chen, Wen; Zhou, Yuan; Lu, Jieyue; Huang, Xusheng; Wu, Wenwei; Lin, Cuiwu; Wang, Qing
Abstract: Co–Mn ferrites with a nominal composition Li x Co0.5 Mn0.5− x Fe2 O4 (0.0≤ x ≤0.3) are prepared by calcining precursor oxalates in air. The effects of composition and calcination temperatures on their structure, morphology, and magnetic properties are studied. A high-crystallized Li x Co0.5 Mn0.5− x Fe2 O4 with a cubic structure is obtained when the precursor is calcined at 950 °C in air for 3 h. All the Li + substituted Co–Mn ferrites exhibit typical spinel structure. Moreover, lattice parameters of Li x Co0.5 Mn0.5− x Fe2 O4 decrease and crystallite size increases with increasing Li + content, leading to an increase of the specific saturation magnetization and a decrease of the coercive field and the magnetic anisotropy constant.